2008
DOI: 10.1017/s0003598x00097623
|View full text |Cite
|
Sign up to set email alerts
|

Middle Palaeolithic bitumen use at Umm el Tlel around 70 000 BP

Abstract: The authors identify natural bitumen on stone implements dating to 70 000 BP. It is proposed that this represents residue from hafting, taking the practice back a further 30 000 years from the date previously noted and published in Nature. The bitumen was tracked to a source 40km away, using gas chromatography-mass spectrometry and carbon isotopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…At low temperatures it is rigid and brittle, at room temperature it is flexible, and at higher temperatures it flows. In contrast to synthetic polymers, a flexible and apolar backbone leads to low glass transition temperatures (Tg) in bitumen (Berkovich et al, 1998;Boëda et al, 2008). The chemistry of bitumen involves saturates (or alkanes), aromatic hydrocarbons (or aromatics) (known as maltenes), resins and asphaltene fractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low temperatures it is rigid and brittle, at room temperature it is flexible, and at higher temperatures it flows. In contrast to synthetic polymers, a flexible and apolar backbone leads to low glass transition temperatures (Tg) in bitumen (Berkovich et al, 1998;Boëda et al, 2008). The chemistry of bitumen involves saturates (or alkanes), aromatic hydrocarbons (or aromatics) (known as maltenes), resins and asphaltene fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of bitumen traces on the surface of several tools from the site of Umm el Tlel of the El Kwom basin in Syria (Boëda et al, 1996(Boëda et al, , 1998(Boëda et al, , 2008 led us to believe that something similar may be found on the pieces from Gura Cheii-Râş nov Cave as well. In order to find the answer to these questions, we considered it necessary to carry out several physicochemical analyses in order to identify the blackish substance present on the two pieces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, poplar found in dental calculus of a Neanderthal from El Sidrón with a dental abscess also demonstrated the likely use of painkillers in the form of salicylic acid, the active ingredient in aspirin (Weyrich et al 2017). More speculatively, the mastery of tar production (Grünberg 2002;Boëda et al 2008; Figure 4. Shanidar Cave, like most cave and rockshelter sites where near complete Neanderthal skeletons have been recovered, is a difficult to access location even for the healthy and fully able.…”
Section: )mentioning
confidence: 99%
“…In Eurasia and Africa, complex technological processes were applied in order to haft MP points (Lombard et al 2005;Shea 1993;Wadley et al 2009). However, flakes and retouched items, not necessarily used in fauna-related activities, were hafted in similar manners (e.g., Boëda et al 2008;Friedman et al 1994-5;Rots 2013;Rots et al 2011). MP stone tools, armatures among them, likely had multiple uses (e.g., Holdaway 1989;Plisson and Beyries 1988;Shea 1988Shea , 1991; and see reviews in Dibble et al 2017;Nelson 1991).…”
Section: A Functional Impassementioning
confidence: 99%